PEMETAAN KETAHANAN PANGAN BERDASARKAN ASPEK KETERSEDIAAN PANGAN DI KOTA PEKANBARU PROPINSI RIAU - Sisca Vaulina; Sri Ayu Kurniati; Sri Mulyani (UIR Press, 2021)
Food availability is food available from natural sources either through food production, cultivating the land, or by other of obtaining food, such as fishing or gathering food. Food availability is important and a priority for food security in Pekanbaru City. The purpose of this research is to map food security based on the aspect of food availability in Pekanbaru City. This research was conducted using the literature study method, used secondary data. Data analysis using FSQ (Food Security Quotient). The results of the study, using calculation of Food Security Quotient (FSQ) in Pekanbaru City, for variables of production and harvested area with a category is very food safe, the commodity is soybeans. Variable food needs, commodities with very safe categories are rice; sweet potato; and peanuts. The aspect of food availability in Pekanbaru City is included in category point V, which is very food safe. The food availability index in Pekanbaru City is a very food-secure condition.